Religious diversity: Looking Eastward: (Asia) beyond the West - Obadia, Lionel; Illman, Ruth (Approaching Religion, 2017)
The subject matter of this special issue is anything but new: religious diversity has already been widely discussed in theology, philosophy, history and sociology. (Too) many times, however, diversity has been measured against the yardstick of the changing face of monotheistic models of religion (mainly Christianity). Asian religions have stood at the opposite end of a spectrum of analytical models in religious studies ever since Max Weber’s classic analysis of Asian religions as mixed systems of beliefs per se. This distinction is, nevertheless, rather problematic, and calls for a closer examination of the conceptual status of diversity, and of the forms it assumes in Asian contexts.